TRADISI KLASIK DALAM PENDIDIKAN ISLAM MODERN (Analisis Kurikulum, Metode, Bahan Ajar Dan Budaya Akademik Di Yayasan Perguruan Islam Al-Kautsar) - Ahmad Ridwan; Rukmana Prasetyo; Ade Rahman Matondang; Fathul Jannah (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
T This research was conducted at Al-Kautsar. The background of this research originates from the researcher's desire to know the classical tradition in Modern Islamic Education at Al-Kautsar. Knowing the classical traditions of education (curriculum, methods, teaching materials and academic culture) is an important part of managing educational institutions to achieve educational goals. This research is categorized into qualitative research. This research intends to bring quality information, therefore in the research report it will be concluded that the findings are qualitative normative. This research was carried out using a descriptive approach, thus the findings will describe what is clear and measurable so that the analysis does not use numbers, but with interpretation of data in the form of words or sentences or other documentation. In addition, this study also emphasizes inductive analysis. mentioning the presence of researchers, research subjects and objects, how to collect research data, location and time of research conducted, and checking the validity of the data. The findings of this study are, the classical tradition in modern Islamic education, the relevance of classical curriculum, classical methods, classical teaching materials and classical academic culture in modern educational institutions.